Effect of a submerged zone and carbon source on nutrient and metal removal for stormwater by bioretention cells - Wang, Mo (2018)
A bioretention system is a low-impact and sustainable treatment facility for treating urban stormwater runoff. To meet or maintain a consistently satisfactory performance, especially in terms of increasing nitrogen removal efficiency, the introduction of a submerged (anoxic) zone (SZ) combined with a module-based carbon source (C) has been recommended. This study investigated the removal of nitrogen (N), phosphorus (P) and heavy metals with a retrofitted bioretention system. A significant (p < 0.05) removal enhancement of N as well as total phosphorus (TP) was observed, in the mesocosms with additions of exogenous carbon as opposed to those without such condition. However, even in the mesocosm with SZ alone (without exogenous C), TP removal showed significant enhancement. With regard to the effects of SZ depth on nutrient removal, the results showed that the removal of both N and P in module with a shallow SZ (200 mm) showed significant enhancement compared to that in module with a deep SZ (300 mm). Removal efficiencies greater than 93% were observed for all three heavy metals tested (Cu, Pb, and Zn) in all mesocosms, even in the bioretention module without an SZ or plants, and it indicated that adsorption by the filtration media itself is probably the most important removal mechanism. Only Cu (but not Pb or Zn) showed significantly enhanced removal in module with an SZ as compared to those without an SZ. Carbon source played a minor role in metal removal as no significant (p > 0.05) improvement was observed in module with C as compared to that without C. Based on these results, the incorporation of SZ with C in stormwater biofilters is recommended.